Concepção semântica da verdade segundo Alfred Tarski - Pereira, Renato Machado (2009)
The objective of this dissertation is analyze the problem of truth as presented by Alfred Tarski in his essay The Semantic Conception of Truth . Other theories of truth are considered, explained and classified in the first chapter. The second chapter attempts provide a general characterization of correspondence theories of truth. Tarski s essay is discussed in the third, and, finally, in the fourth chapter, the semantic and correspondence theories are compared, and the philosophical importance of the former is evaluated.